Synergistic effect of glass bead and glass fiber on the crystalline structure, thermal stability, and mechanical, rheological, and morphological properties of polyamide 6 composites - Kuram, Emel (Sage Publications Ltd, 2022)
The effect of filler amount and kind on the crystalline structure, thermal stability, and mechanical, rheological, and morphological properties of polyamide 6 (PA6) was studied in this research. Glass bead and glass fiber were chosen as mineral fillers. They were incorporated to PA6 solely or in mixed formulations at different proportions (hybrid composites). Tensile strain, tensile strength, impact strength, flexural strain, flexural strength, melt flow index, crystallite size, and thermal degradation parameters were determined for all composites. The addition of glass bead or glass fiber increased the brittleness of pure PA6. The incorporation of glass fiber to pure PA6 improved flexural, impact, and tensile strengths, and mixing of glass bead with pure PA6 polymer caused deterioration of both (tensile and flexural) strengths, but enhanced impact strength. Among hybrid composites, the highest flexural, tensile, and impact strength values were achieved with 15 wt% glass bead and 15 wt% glass fiber content. The addition of glass bead and/or glass fiber to PA6 polymer caused a decrement in melt flow index value. X-ray diffraction results indicated that pure PA6 polymer had alpha- and gamma-crystalline forms, and the reinforcement of glass bead or glass fiber would induce the crystallization into gamma-form. It was also found that the incorporation of glass bead or glass fiber influenced the lamellar thickness, and pure PA6 gave thicker lamellar crystal than that of glass bead/fiber-reinforced PA6 and its hybrid composites. Higher thermal stability with glass bead or glass fiber incorporation was found as compared to pure PA6 polymer.
Keywords: hybrid composite; mechanical properties; injection molding